2016
DOI: 10.5114/pm.2016.63500
|View full text |Cite
|
Sign up to set email alerts
|

The significance of markers in the diagnosis of endometrial cancer

Abstract: Endometrial cancer is one of the most common cancers experienced by women throughout the world. It is also the most common malignancy within the female reproductive system, representing 37.7% of all disorders. The incidence increases with age, and is diagnosed most frequently in women between 45 and 65 years old. In the last few years, numerous studies have been performed to identify tumour biomarkers. Biomarkers include not only protein routinely used as tumour markers but also genes and chromosomes. The limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 101 publications
(101 reference statements)
0
11
0
Order By: Relevance
“…The most used biomarker is circulating CA 125 but not only is the sensitivity unsatisfactory, especially in early tumor stage, but also its specificity is low. Nevertheless CA125 has no correlation with the prognosis of the patient [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most used biomarker is circulating CA 125 but not only is the sensitivity unsatisfactory, especially in early tumor stage, but also its specificity is low. Nevertheless CA125 has no correlation with the prognosis of the patient [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 5 , 10 , 11 However, inconsistent results have been published and there is no consensus on whether serum tumor markers are of diagnostic or prognostic importance in EC. Studies examining serum CA15-3 levels in EC patients 2 - 5 , 12 , 15 were also found to be inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…It is being thought that severe military conflicts in Africa shorten the expected lifetime for more than 2 years. In general, WHO had calculated that 269 thousand people had died in 1999 due to the effect of wars and that loss of 8.44 million healthy years of life had occurred (2,3). Wars negatively affect the provision of health services.…”
Section: War and Women's Healthmentioning
confidence: 99%